Inspirasi Kisah Dalam Menstimulasi Character Building Anak Usia Dini - Mariana, Mariana (ACIECE, 2018)
This study aims to describe the story method to provide a stimulus for the planting of earlychildhood characters. The method used is descriptive-qualitative. Primary research data oreeight early childhood and parents who live in the village of Pulosari Jambon Ponorogo. Datacollection techniques include observation,interviews and documentation. Data analysis usinggrounded research. The results of this study are that there are character education values in thecartoon story uuupin ipin. The character of the character in the cartoon film provides a stimulusto instill the character of early childhood in accordance with the development of children so thatit can provide an effective example in fostering the character or early childhood